2010
DOI: 10.1177/0748233710381892
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of heavy metals in mullet (Mugil cephalus) and oyster (Crassostrea madrasensis) from Pulicat lake, south east coast of India

Abstract: The accumulation of six heavy metals (Cr, Cd, Cu, Zn, Pb and Ni) in sediment, water and in tissue parts of Mugil cephalus and Crassostrea madrasensis was studied in two locations of Pulicat lake, Southeast coast of India, which receives considerable quantity of effluents from industries located in North Chennai coastal region. The results reveal that the metal concentration in water is decreasing in the following order of Zn > Ni > Cu > Cr > Pb > Cd both in lake and barmouth and highest concentration was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Several authors have previously investigated the feeding habits and heavy metal distributions in grey mullet ( M. cephalus ), since this fish species lives close to the bottom sediments [ 55 , 56 , 57 , 58 , 59 ]. They found that the mullet specimens accumulate heavy metals in various tissues, and this is a prominent indicator for the heavy metal pollution coming from the surrounding water bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have previously investigated the feeding habits and heavy metal distributions in grey mullet ( M. cephalus ), since this fish species lives close to the bottom sediments [ 55 , 56 , 57 , 58 , 59 ]. They found that the mullet specimens accumulate heavy metals in various tissues, and this is a prominent indicator for the heavy metal pollution coming from the surrounding water bodies.…”
Section: Discussionmentioning
confidence: 99%
“…The natural water bodies may extensively be contaminated with various heavy metals released from industrial and mining effluents, discharge of sewage and sewage sludge, dumping of hospital and anthropogenic activities, etc. (Vinodhini & Narayanan, 2008;Malik et al, 2010;Laxmi-Priya et al, 2011 andMohamed, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Both species are highly regarded among the Gumbaynggirr community for cultural, customary, and sustenance purposes, in both a historic and contemporary context. However due to their feeding techniques, both species have a high capacity for bioaccumulation of contaminants [ 25 27 ]: Oysters filter large quantities of water [ 28 ] and the fish family, Mugilidae, to which M . elongatus belong are largely detritivores [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trace metals persist in the environment and exist within aquatic ecosystems from natural and anthropogenic origins [ 28 31 ]. They are widespread and have a tendency to accumulate in the tissue of many aquatic animals [ 28 , 32 , 33 , 34 , 35 ]. Presence of trace metals in the Nambucca River estuary may be due to the influence of derelict mines, agriculture, cattle dips and mineralization in the catchment [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%